Long-term variations of river ice breakup timing across Canada and its response to climate change - Chen, Yuzhuang; She, Yuntong (Cold Regions Science and Technology, 2020)
Abstract River ice breakup has extensive implications on cold-region hydrological, ecological and river morphological systems. However, spatial and temporal breakup patterns under the changing climate are not well explored on large scale. This study discusses the spatial-temporal variations of breakup timing over terrestrial ecozones and five selected river basins of Canada based on long-term (1950–2016) data record. The link between the discovered patterns and climatic drivers (including air temperature, snowfall and rainfall), as well as elevation and anthropogenic activities are analyzed. An overall earlier breakup trend is observed across Canada and the spring air temperature is found to be the main driver behind it. However, the most pronounced warming trends across Canada is observed in winter. Spring warming trend is not as strong as winter warming and even becomes weak as period changes from 1950–2016 to 1970–2016, resulting in more stations showing later and significant later breakup during 1970–2016. Breakup pattern also displays evident spatial differences. Significant earlier breakup trends are mainly seen in western Canada (e.g. the Nelson River basin) and Arctic where spring warming trends are evident. Later and mixed breakup trends are generally identified in regions with weak warming or even cooling trends, such as Atlantic Canada and the St. Lawrence River basin. Spring snowfall generally delays breakup. Spring rainfall usually advances breakup dates while winter-rainfall can also delay breakup through refreezing. The increased snowfall in the north and increased rainfall in the south may be the reason why breakup timing is more sensitive to climatic warming in lower latitude regions than in higher latitude regions. Additionally, breakup timing in main streams and large rivers appears to be less sensitive to the warming trend than the headwaters and small tributaries. Elevation and flow regulation are also found to be contributing factors to the changes in breakup timing.